2016
DOI: 10.1108/aeat-03-2014-0030
|View full text |Cite
|
Sign up to set email alerts
|

Aerodynamic characteristics of a wrap-around fin rocket

Abstract: Purpose – The purpose of this paper is to investigate the aerodynamics characteristics (especially the side force/moment and rolling characteristics), to analyze the impacts generated by different parameters of wrap-around fins (WAFs) and to find the corresponding mechanism. Design/methodology/approach – The paper has adopted three different types of WAFs for the rocket configurations and the sub-regions divided technology to investigate the lateral and rolling characteristics of WAFs, including the fins … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…This is further investigated in various literature. 8 10–12,14,15 . However, it is observed that, by positioning the fins in an opposite arrangement, identical pressure distributions develop on either sides of the fin, ending up with the elimination of the rolling moment, so that the objective of the present research (elimination of rolling moment) is achieved.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is further investigated in various literature. 8 10–12,14,15 . However, it is observed that, by positioning the fins in an opposite arrangement, identical pressure distributions develop on either sides of the fin, ending up with the elimination of the rolling moment, so that the objective of the present research (elimination of rolling moment) is achieved.…”
Section: Resultsmentioning
confidence: 99%
“…Further, Zhang et al. 14 showed the span length and chord size are two main factors for controlling the longitudinal features. Zhang et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[14][15][16][17][18][19][20][21][22][23] Our previous studies only focus on the qualitative and quantitative analysis for different Wrap-around fins (N ¼ 4, 6 and 8) by drawing the orthogonal tables for different parameters. 24 The current research will mainly focus on the characteristics comparisons between the flat fins and WAFs. The parametric studies on the flat fins and WAFs configurations are conducted, including the span to chord ratio, curvature radius as well as setting angles.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the above methods, CFD is the kind of simulation method by which we can intuitively get the distribution of the flow field, and for the reasons that the process is simple and the results reliable and accurate, it is widely used for aerodynamic parameter calculations of guided projectiles, resulting in it becoming a hot area of aerodynamic research. For example, the CFD simulation has been used for the aerodynamic characteristic study of the spin-stabilized artillery shell by Hamel and Gagnon, 1 Je et al, 2 Fu et al, 3 and Yin et al, 4 used for the aerodynamic characteristic study of the fin-stabilized rocket by Afzal et al, 5 Sahu,6 Zhimin et al, 7 Sahu et al, 8 Zhang et al, 9 and López et al, 10 and used for the aerodynamic characteristic study of the mortar projectile by Su et al, 11 Li et al, 12 and Chengen et al 13 Most of the CFD simulations that are used for aerodynamic characteristic studies on projectiles, are focused on the effect of geometry on the aerodynamic parameter. The contrastive analysis of the CFD simulation method is relatively less.…”
Section: Introductionmentioning
confidence: 99%